New Developments and Advances in Robot Control - Derbel, Nabil; Ghommam, Jawhar; Zhu, Quanmin; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2019)
This book highlights relevant studies and applications in the area of robotics, which reflect the latest research, from interdisciplinary theoretical studies and computational algorithm development, to representative applications. It presents chapters on advanced control, such as fuzzy, neural, backstepping, sliding mode, adaptive, predictive, diagnosis and fault tolerant control etc. and addresses topics including cloud robotics, cable-driven robots, two-wheeled robots, mobile robots, swarm robots, hybrid vehicle, and drones. Each chapter employs a uniform structure: background, motivation, quantitative development (equations), case studies/illustration/tutorial (simulations, experiences, curves, tables, etc.), allowing readers to easily tailor the techniques to their own applications.
Canonical Particle Swarm Optimization Algorithm Based a Hybrid Vehicle -- Control of Robot Manipulators using Modified Backstepping Sliding Mode -- Robot Manipulator Control using Backstepping with Lagrange's Extrapolation and PI Compensator -- Cloud Robotics : Opening a new road to the Industry 4.0 -- Cable-Driven Parallel Robot Modelling for Rehabilitation Use -- Nonlinear Observer-Based Fault Detection and Isolation for a Manipulator Robot -- Digital stabilizing and control for two-wheeled robot -- Mobile Robot Path Planning based on Optimized Fuzzy Logic Controllers -- 4×2D Visual Servoing Approach for Advanced Robot Applications -- A Redundant Parallel Robotic Machining Tool: Design, Control and Real-Time Experiments -- Design and Implementation of a Reactive Navigation System for a Smart Robot Using Udoo Quad -- Backstepping-Based Nonlinear RISE Feedback Control for an underactuated Quadrotor UAV without Linear Velocity Measurements -- Area Coverage Algorithms for Networked Multi-Robot Systems -- Cartesian Sliding Mode Control of an Upper Extremity Exoskeleton Robot for Rehabilitation -- Crone controller design for a position servo used in robotics.
Keywords: Control engineering; Robotics; Automation; Multibody systems; Vibration; Mechanics, Applied; System theory; Mathematics; Artificial intelligence; Control and Systems Theory; Control, Robotics, Automation; Multibody Systems and Mechanical Vibrations; Complex Systems; Applications of Mathematics; Artificial Intelligence